The Nordic Postmodernism : Collection : Watercolours, graphic art and drawings. - Purhonen, Tiina; Robbins, Nina (Helsinki : KIASMA Museum of Contemporary Art, 2000)
The contents of The Nordic Postmodernism exhibition are divided into four themes : High & Low - the unholy couple of art, Sexuality - identities, Multiple Historical Layers - fragmentation and Death of the Artist - anonymous art. Through these themes postmodernism in Nordic art from the 1980s on, what it has achieved and what parts of it have remained alive can all be looked at. The same postmodernist themes are represented in the works exhibited in Printti, but here they run parallel to traditions of artistic technique, and the postmodern is forced into a dialogue with these traditions. All works in the exhibition have been selected from the Museum of Contemporary Art Kiasma's own collection.
Anttila, Lauri ; Haarla, Teuri ; Hafström, Jan ; Huhta, Jari ; Hukkanen, Reijo ; Immonen, Teija ; Isomaa, Eeva-Liisa ; Jämsä, Aarne ; Jenssen, Olav Christopher ; Kallio, Païvikki ; Lavonen, Kuutti ; Lehtinen, Tuula ; Luostarinen, Leena ; Mikkonen, Tapani ; Niva, Jussi ; Puha, Tero ; Rantanen, Silja ; Rasmussen, Hans Hamid ; Suomi, Risto ; Tanttu, Antti ; Tom of Finland ; Väisänen, Hannu ; Varis, Hanna
Engels
The Nordic Postmodernism : Collection : watercolours, graphic art and drawings, KIASMA (Museum of Contemporary Art) Helsinki, 12.9.2000 - 19.8.2001
boek